INDIVIDUAL AND GROUP WORK METHODS IN TEACHING LANDSCAPE DRAWING TO ART SCHOOL STUDENTS - Amonova Durdona Aliek qizi (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2026)
This article explores individual and group work methods in teaching landscape drawing to art school students. The study emphasizes the importance of balancing personalized instruction with collaborative activities to enhance students’ technical skills, creativity, and visual thinking. Individual tasks focus on developing personal strengths, addressing weaknesses, and fostering independent artistic expression. Group activities promote collaboration, peer feedback, and collective problem-solving, encouraging students to learn from one another and expand their creative perspectives. The article highlights effective strategies for integrating these methods into landscape drawing lessons to improve both cognitive and artistic development.